Preparation, characterization, and properties of disulfide-containing polyethyleneimine grafted carbon nanotubes. Issue 6 (3rd June 2017) - Zhang, Qiao; Lei, Ming; Huang, Shuwen; Fu, Huili; Yan, Guoping; Li, Liang; Yan, Huizhen
ABSTRACT: Novel functionalized carbon nanotubes (CNTs) were prepared by grafting disulfide-containing polyethyleneimine (SSPEI) to CNTs. The SSPEI were synthesized by Michael addition between cystamine bisacrylamide and low molecular weight branched 1.8 kDa PEI. Three SSPEI grafted carbon nanotubes (CNTs-SSPEI) were successfully prepared through grafting SSPEI to CNTs. The grafted ratios were 32.26%, 43.11%, and 51.50%, respectively. Moreover, the grafted ratio could be tuned by adjusting the CNTs/SSPEI ratio during the process of preparation. The CNTs-SSPEI was characterized using Fourier transform infrared spectroscopy, scanning electron microscopy and thermogravimetric analysis. The CNTs-SSPEI showed better dispersability and stability in water than CNTs. In addition, the SSPEI on the surface of CNTs-SSPEI could be degraded in the presence of dithiothreitol.